Total factor productivity and economic efficiency in the Gulf cooperation council (GCC) countries - Alamedin A. Bannaga; Mohammed Lezar (Cogent Economics & Finance, 2024)
This study focuses on identifying the level and evolution of total factor productivity (TFP) and determining its role as a qualitative source of economic growth in the Gulf Cooperation Council (GCC) countries. This is an issue of particular importance because of the recent increases in external global crises, such as the Covid-19 pandemic, and large fluctuations in oil prices. In addition, there are existing internal challenges in the GCC countries, such as high rates of population growth, labor market pressures, a large-sized public sector, and an inefficient private sector. These challenges require achieving a qualitative improvement in the sources of economic growth by raising the efficiency of the use of available productive resources through relying on the growth of TFP as a primary driver of sustainable economic growth. The results of the study showed that the growth rates in TFP were generally negative and below the average international levels. This can be attributed to several reasons such as weak innovation and the adoption of a stagnant development model. The study presents some recommendations to address these challenges. Productivity plays a crucial role in the economic and social progress of nations. Economic growth in the GCC countries faces numerous challenges, including fluctuating oil prices, the rapid growth of the working-age population, stagnant productivity in the public sector, and geopolitical risks in the region. These challenges have made it increasingly difficult for these countries to rely heavily on oil revenues, highlighting the importance of transitioning to an economic model that emphasizes sustainable sources of growth. This shift involves raising productivity to create new economic dynamism, diversify income sources, and respond effectively to current and future market changes. In this study, we focus on Total Factor Productivity (TFP) analysis for several reasons: TFP is often interpreted as a measure of technological progress or innovation; it reflects better management practices; it can be used to assess the impact of various policies on economic efficiency; changes in TFP can help in understanding the sources of economic fluctuations and resilience; and it indicates the quality of policies and institutions that are fundamental to economic growth. By emphasizing TFP, the GCC countries can align their strategies with long-term visions such as Saudi Arabia's Vision 2030 and the UAE's Centennial 2071.
Keywords: 330; empirical evidence; GCC countries; sources of economic growth; Total factor productivity